(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Background: health informatics have bene used in the field healthcare for quite a long time. Research investigations have since been conducted to examine various features around the use and application of health informatics. However, there is an apparent gap in the current literature in regard to comprehensive information about the effect of health informatics on the healthcare workers’ practices in Saudi German Hospital, Jeddah. Aim: the aim of this research was to evaluate the implication of health informatics on the healthcare workers’ activities in Saudi German Hospital in Jeddah, Saudi Arabia. Methods: this study applied cross-sectional quantitative research design. Upon seeking and receiving the ethical approval, a sample of 123 sample of healthcare workers in Saudi German Hospital, Jeddah were recruited for data collection. Henceforth, data was collected using survey questionnaires, to which 105 (85.3%) responses were received. The collected data was then analyzed using three statistical tools of SPSS, including the descriptive statistics, Spearman’s rank correlation coefficient, multiple linear regression and multiple analysis of variance. Results: this study found out that health informatics has two critical roles regarding the healthcare workers practices. This was indicated by 40.9% of the participants who strongly agreed that health informatics augments quality of healthcare services delivery and 41.9% of the participants who strongly agreed that health informatics enhances information quality. This study further established that health informatics has a statistically significant impact on the quality of patient care (r=502; p=.000), health workers competencies (r=522; p=.000), and patient safety (r=457; p=.000). Further, this research also observed that the perceived roles of health informatics was had statistically significant association with the healthcare workers’ age (p=.023) and education level (p=.033). Recommendation: there is a need for the healthcare administrations units to intensify the use of health informatics to improve the quality of healthcare service delivery as a function of the healthcare workers.